Efeitos da neblina no sistema de comunica??es ?pticas no espa?o aberto - Almeida , Indira Mar?lia Ant?nio de (2017)
Free space optics (FSO) communication systems are characterized by the transmission of information applying optical propagation through the atmosphere. It is a promising technology for wireless broadband networks and an alternative to be used in conjunction with radiofrequency (RF) and optical fiber systems. However, the performance of this technology is dependent on the conditions of the beam propagation medium. Atmospheric factors, such as fog, water droplets, dust concentration and aerosol particles, produce absorption and scattering causing a degradation in the optical link. This dissertation presents the concepts and limitations of FSO system. An optical link was evaluated with the transmission channel under the influence of the fog. Two wavelengths were used, one in the visible range 532nm and another in the near infrared 1550nm. Attenuations in the fog were obtained for different degrees of relative humidity at those wavelengths. It was analyzed the temporal dispersion ultrashort pulses and the effects on the eye diagram. In the analysis of the performance of the link it was obtained the bit error rate (BER) by the factor that measures the quality of the eye (Q). The value of the BER in the fog showed that signal is acceptable for data transmission, although complying with the limit of forward error correction (FEC).